A Case of Hyperimmunoglobulinemia D Syndrome Successfully Treated with Canakinumab - Elena Tsitsami (Case Reports in Rheumatology, 2013)
Hyperimmunoglobulinemia D syndrome is a rare autosomal recessive autoinflammatory disorder caused by mutations in the mevalonate kinase gene (MVK). In a proportion of patients, however, no MVK mutations are detected. Although various standard anti-inflammatory drugs have been tried, until now there is no consensus about how HIDS should be treated. We present a case of HIDS in an 8-year-old girl whose clinical picture had started before the end of the first year of life. The patient had consistently elevated IgD levels but no mutations were found after a full-length analysis of the MVK gene. The method of MVK mutational analysis is presented in details. Treatment with canakinumab in a final single dose of 4 mg/kg every 4 weeks resulted in the disappearance of febrile attacks and a considerable improvement of patients’ quality of life during a 12-month follow-up period. The drug has been well tolerated, and no side effects were observed.